Glucocorticoid effects in the regenerating fin reflect tissue homeostasis disturbances in zebrafish by affecting Wnt signaling - Fleischhauer, Lisa; López-Delgado, Alejandra Cristina; Geurtzen, Karina; Knopf, Franziska (Frontiers in Endocrinology, 2023)
As a treatment for various immune-mediated diseases, the use of glucocorticoids as anti-inflammatory and immunosuppressive agents is common practice. However, their use is severely hampered by the risk of the development of adverse effects such as secondary osteoporosis, skin atrophy, and peptic ulcer formation. The exact molecular and cellular mechanisms underlying those adverse effects, which involve most major organ systems, are not yet fully understood. Therefore, their investigation is of great importance to improve treatment regimens for patients. Here, we investigated the effects of the glucocorticoid prednisolone on cell proliferation and Wnt signaling in homeostatic skin and intestinal tissue and compared them to the anti-regenerative effects in zebrafish fin regeneration. We also investigated a potential recovery from the glucocorticoid treatment and the impact of short-term treatment with prednisolone. We identified a dampening effect of prednisolone on Wnt signaling and proliferation in highly proliferative tissues, namely the skin and intestine, as well as reduced fin regenerate length and Wnt reporter activity in the fin. The presence of the Wnt inhibitor Dickkopf1 was enhanced in prednisolone treated skin tissue. A decreased number of mucous producing goblet cells was observed in the intestine of prednisolone treated zebrafish. Unexpectedly, proliferation in bone forming osteoblasts of the skull, homeostatic scales, as well as the brain was not decreased, opposite to the observed effects in the skin, fin, and intestine. Short-term treatment with prednisolone for a few days did not significantly alter fin regenerate length, skin cell proliferation, intestinal leukocyte number and proliferation of intestinal crypt cells. However, it affected the number of mucous-producing goblet cells in the gut. Likewise, discontinuation of prednisolone treatment for a few days saved the skin and intestine from a significant reduction of skin and intestinal cell proliferation, intestinal leukocyte number and regenerate length, but did not rescue goblet cell number. The suppressive effects of glucocorticoids in highly proliferative tissues may be relevant in the context of their therapeutic applications in patients with inflammatory diseases.